A typical case of resected pancreatic hamartoma: a case report and literature review on imaging and pathology - Hokahiro Katayama; Kyohei Azuma; Kenji Koneri; Makoto Murakami; Yasuo Hirono; Satomi Hatta; Yoshiaki Imamura; Takanori Goi (Surgical Case Reports)
Abstract Background Pancreatic hamartomas are rare entities and difficult to diagnose before resection. We report a case of resected pancreatic hamartoma and literature review of typical characteristics of the lesion. Case presentation A 78-year-old man presented with a mass in his pancreas, which was incidentally identified when he experienced pneumonia. No remarkable symptoms were observed, and laboratory tests showed no abnormalities, except a slight carcinoembryonic antigen elevation. Enhanced computed tomography and magnetic resonance imaging showed a well-demarcated solid mass with heterogeneous contrast that was 2 cm in size. A gradual enhancement pattern was also observed. The biopsy revealed no specific findings; therefore, surgical resection was necessitated to confirm the diagnosis. Histopathologically, ducts, acinar cells, and adipose cells without atypia were observed among abundant fibrous stroma, but islets of Langerhans and peripheral nerves were absent. An immunohistochemical examination demonstrated CD34 and c-kit positive staining in the stromal cells, S-100 positivity in the adipose cells, and a lack of elastic fibers in the duct walls. The lesion was diagnosed as a pancreatic hamartoma. Conclusion Asymptomatic pancreatic hamartomas can avoid resection. A careful consideration of imaging and appropriate immunohistochemistry of biopsy specimen may facilitate accurate diagnosis before resection. Therefore, sufficient recognition of the characteristics of pancreatic hamartomas is desirable.